Process Characteristics of Horizontal Log Band Saw in Cutting Frozen Beech - Mikuláš Siklienka (University of Zagreb, Faculty of Forestry and Wood Technology, 2015)
The paper presents the research results of process characteristics during cutting beech prisms on horizontal log band saw type Mebor HTZ–1000. The band saw blades were equipped with swaged teeth and stellited teeth. The power consumption, tool wear resistance, surface roughness and variation of board thickness during 6000 m sawn prism length were studied. All studied parameters were monitored during the tool life-circle (from sharpening to loosing its sawing capability). Wearing process was monitored as a function of cutting length. The cutting edge modifi cation, i.e. its wearing affecting energetic demands during sawing process as well as the surface quality and dimension accuracy of produced work piece was monitored, too. Based on cutting edge wear process and its effect on the above mentioned sawing process parameters, the optimal period of saw band replacement with a new or sharpened one was determined. Based on measured parameters, it was possible to determine which type of band saw tooth is recommended for cutting frozen beech.